2022
DOI: 10.3390/agronomy12102569
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fractions in Temperate Grassland Soils and Their Interactions with Agronomic P Tests

Abstract: Phosphorus (P) is a major nutrient for plant growth and animal health, and its availability in soil is influenced by agronomic management and soil properties. This study examined the distribution of labile and non-labile soil P fractions in grassland and the properties that influence their distribution in temperate grasslands. Eleven fractions were identified as, labile (H2O.P and NaHCO3.P), moderately labile (NaOH.P) and plant non-available (NaOH.P, HCl.P and residual P). The residual P, moderately labile org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In studies on grasslands receiving no P fertilizer application, Pi–NaOH concentrations amounted, at most, to approximately one‐third of the concentrations found in our study. In general, fertilized grasslands, including Finnish cattle farms (Uusitalo et al., 2007), have also been found to have lower Pi–NaOH concentrations than the soils in our study, ranging from 130 to 259 mg kg −1 (Condron & Goh, 1989; Crews & Brookes, 2014; Graça et al., 2022; Pätzold et al., 2013; Sharpley et al., 2004). According to the Finnish fertilizer application recommendations, the Maaninka and Ruukki fields had not received excessive fertilizer application before the start of the experiments, but the labile and moderately labile P concentrations, almost approaching the level observed in Sharpley's (2004) heavy fertilizer application experiment, were the result of common Finnish cultivation practices.…”
Section: Discussionsupporting
confidence: 49%
“…In studies on grasslands receiving no P fertilizer application, Pi–NaOH concentrations amounted, at most, to approximately one‐third of the concentrations found in our study. In general, fertilized grasslands, including Finnish cattle farms (Uusitalo et al., 2007), have also been found to have lower Pi–NaOH concentrations than the soils in our study, ranging from 130 to 259 mg kg −1 (Condron & Goh, 1989; Crews & Brookes, 2014; Graça et al., 2022; Pätzold et al., 2013; Sharpley et al., 2004). According to the Finnish fertilizer application recommendations, the Maaninka and Ruukki fields had not received excessive fertilizer application before the start of the experiments, but the labile and moderately labile P concentrations, almost approaching the level observed in Sharpley's (2004) heavy fertilizer application experiment, were the result of common Finnish cultivation practices.…”
Section: Discussionsupporting
confidence: 49%
“…We chose to compare ambient to enriched nutrient levels to test the degree to which predicted increases in N and P from anthropogenic activity preferentially favor one cytotype over others. The vermiculite–potting soil mix contained 55 ppm N (μg N g −1 ) and 12.5 ppm P (μg P g −1 ), and we designated this mixture as the ambient N and P treatments because the nutrients were similar to N and P levels reported in global grassland ecosystems (e.g., dissolved available N range reported as 15–65 ppm, Christou et al 2005; dissolved available P range reported as 1.2–29.0 ppm, Graça et al 2022). For the enriched treatments, we added nutrients to pots to achieve enriched treatments with 110 ppm N (μg N g −1 ) or 25 ppm P (μg P g −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…While the relative contribution of the biotic P influx decreased with SSP application in agreement with previous IPD studies, we also observed a slight increase in relative contribution of the P immobilization rate in the P balanced and excess P soils. This observation could be caused by the difference between the microbial community structure in the soils without P limitation (Griffiths et al, 2012) and could be associated with higher P immobilization due to an increased biological activity in the soil receiving an excessive amount of nutrients and a shift of the microbial community towards a bacterial dominated (Graça, 2018).…”
Section: Physicochemical and Biological Controls Of Soil P Cycle Cont...mentioning
confidence: 99%